2013
DOI: 10.1021/ac401536g
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport in a pH-Regulated Nanopore

Abstract: Fundamental understanding of ion transport phenomena in nanopores is crucial for designing the next-generation nanofluidic devices. Due to surface reactions of dissociable functional groups on the nanopore wall, the surface charge density highly depends upon the proton concentration on the nanopore wall, which in turn affects the electrokinetic transport of ions, fluid, and particles within the nanopore. Electrokinetic ion transport in a pH-regulated nanopore, taking into account both multiple ionic species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(201 citation statements)
references
References 58 publications
11
190
0
Order By: Relevance
“…This charge regulation effect not only affects nanochannels modified by pH-responsive polyelectrolytes but also systems where the inner walls have weak acid or basic groups. The later situation was analyzed by Yeh et al using numerical calculations [44] and analytical theory [45]. These works showed that charge regulation is coupled to the polarization concentration effect, which results in gradients of pH and degree of protonation along the axis of the pore [44].…”
Section: Chemically Gated Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This charge regulation effect not only affects nanochannels modified by pH-responsive polyelectrolytes but also systems where the inner walls have weak acid or basic groups. The later situation was analyzed by Yeh et al using numerical calculations [44] and analytical theory [45]. These works showed that charge regulation is coupled to the polarization concentration effect, which results in gradients of pH and degree of protonation along the axis of the pore [44].…”
Section: Chemically Gated Ion Channelsmentioning
confidence: 99%
“…The later situation was analyzed by Yeh et al using numerical calculations [44] and analytical theory [45]. These works showed that charge regulation is coupled to the polarization concentration effect, which results in gradients of pH and degree of protonation along the axis of the pore [44]. Figure 2e shows that the charge carriers inside the nanochannel at low pH are almost exclusively Cl À ions and, hence, the anion selectivity (current carried by the anions over the total current) is very high.…”
Section: Chemically Gated Ion Channelsmentioning
confidence: 99%
“…When the electrolyte was at higher pH value, the additional OH -were repelled by the cation-selective membrane, but might associate with H 2 O to form H 3 O 2 -28,29 . According to previously studies [30][31][32][33] , results indicated the spatial variation of surface charge density strongly depends on bulk concentration and pH value. The surface charge density increases with increasing the pH value due to the H + ion concentration is high in the Nafion membrane.…”
Section: ≈ D Dmentioning
confidence: 67%
“…The pressure-driven flow is directed in the y-direction and E str is induced in the opposite flow direction. Note that the effect of ion concentration polarization [24,25], arising from the selective transport of ions in nanofluidics, is neglected, which is appropriate when the nanochannel is sufficiently long.…”
Section: Mathematical Modelmentioning
confidence: 99%